COMPARISON OF URETERO RENOSCOPIC (URS) LITHOTRIPSY WITH AND WITHOUT DJ STENTING IN MID AND DISTAL URETERIC STONE. - Syed Atif Hussain (Journal of University Medical & Dental College, 2018)
ABSTRACT:OBJECTIVE: The objective of the study was “To compare the eﬃcacy of Ureterorenoscopic (URS) lithotripsy with and without DJ stenting in mid and distal ureteric stone. INTRODUCTION:Ureteric stenting following fragmentation of stone is routine in most of the centers, however their overuse has been questioned because their use is not free of complications and problems. Literature review reveals that post ureterorenoscopic lithotripsy, DJ Stent insertion does not support the idea of routine DJ Stent placement in every patient. MATERIALS & METHODS:A total of 60 patients with single ureteric stone in mid or distal ureter, 20 to 60 years of age of both genders were included. Patients with h/o previous open ureterolithotomy, any chronic disease and urinary disorders were excluded. Patients were divided in two groups, 30 patients in each group by randomised method. Patients in group A underwent URS lithotripsy without DJ stenting and those in group B underwent URS lithotripsy with DJ stenting. Patients were followed till one month and eﬃcacy (in terms of 100% clearance rate) and complication rate was assessed. RESULTS: The mean age of patients in group A was 39.21 ± 6.83 years and in group B was 38.78 ± 6.91 years. Out of 60 patients, 41 (68.33%) were males and 19 (31.67%) were females with male to female ratio of 2.16:1. Eﬃcacy (100% clearance rate at 1 month and no post-operative complication) of URSL without DJS was 83.33% while in URSL with DJS was 56.67% with p-value of 0.024 which is statistically signiﬁcant. CONCLUSION: This study concluded that eﬃcacy (in terms of stone clearance and complication rate) of URS lithotripsy without DJ stenting is higher compared to with DJ stenting in mid and distal ureteric stone.